How Different are the Diamagnetic and Paramagnetic Contributions to Off‐Nucleus Shielding in Aromatic and Antiaromatic Rings?. Issue 9 (9th March 2023) - Karadakov, Peter B.
Abstract: The spatial variations in the diamagnetic and paramagnetic contributions to the off‐nucleus isotropic shielding, σ i s o r = σ i s o d r + σ i s o p r ${\ {{σ }_{{\rm i}{\rm s}{\rm o}}\left({\bf r}\right)=\ σ }_{{\rm i}{\rm s}{\rm o}}^{{\rm d}}\left({\bf r}\right)+{σ }_{{\rm i}{\rm s}{\rm o}}^{{\rm p}}\left({\bf r}\right)}$, and to the zz component of the off‐nucleus shielding tensor, σ z z r = σ z z d r + σ z z p r ${{{σ }_{zz}\left({\bf r}\right)=σ }_{zz}^{{\rm d}}\left({\bf r}\right)+{σ }_{zz}^{{\rm p}}\left({\bf r}\right)}$, around benzene (C6 H6 ) and cyclobutadiene (C4 H4 ) are investigated using complete‐active‐space self‐consistent field wavefunctions. Despite the substantial differences between σ i s o r ${{σ }_{{\rm i}{\rm s}{\rm o}}\left({\bf r}\right)}$ and σ z z r ${{σ }_{zz}\left({\bf r}\right)}$ around the aromatic C6 H6 and the antiaromatic C4 H4, the diamagnetic and paramagnetic contributions to these quantities, σ i s o d r ${{σ }_{{\rm i}{\rm s}{\rm o}}^{{\rm d}}\left({\bf r}\right)}$ and σ z z d r ${{σ }_{zz}^{{\rm d}}\left({\bf r}\right)}$, and σ i s o p r ${{σ }_{{\rm i}{\rm s}{\rm o}}^{{\rm p}}\left({\bf r}\right)}$ and σ z z P r ${{σ }_{zz}^{{\rm P}}\left({\bf r}\right)}$, are found to behave similarly in the two molecules, shielding and deshielding, respectively, each ring and its surroundings. The different signs of the most popular aromaticity criterion, the nucleus‐independent chemical shift (NICS), in C6 H6 and C4 H4 are shown to follow from a change in the balance between the respective diamagnetic and paramagnetic contributions. Thus, the different NICS values for antiaromatic and antiaromatic molecules cannot be attributed to differences in the ease of access to excited states only; differences in the electron density, which determines the overall bonding picture, also play an important role. Abstract : Analysis of the diamagnetic and paramagnetic contributions to off‐nucleus shielding in benzene and cyclobutadiene shows that the different off‐nucleus shielding pictures and nucleus‐independent chemical shift (NICS) values for antiaromatic and antiaromatic molecules cannot be attributed to differences in the ease of access to excited states only; differences in the electron density, which determines the overall bonding pattern, also play an important role.